2022
DOI: 10.1155/2022/7251460
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Tactile Stimulation Downregulates Dendritic Spines in Layer V Pyramidal Neurons of the WAG/Rij Rat Somatosensory Cortex

Abstract: Objective. The aim of our study is to examine the effects of neonatal tactile stimulations on the brain structures that previously defined as the focus of epilepsy in the Wistar-Albino-Glaxo from Rijswijk (WAG/Rij) rat brain with genetic absence epilepsy. Methods. In the present research, morphology and density of dendritic spines were analyzed in layer V pyramidal neurons of the somatosensory cortex (SoCx) of WAG/Rij rats (nonstimulated control, tactile-stimulated, and maternal separated rats) and healthy Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a study done by our group we found that neonatal tactile stimulation slows down the development of absence epilepsy and comorbid depression-like symptoms in adult WAG/Rij rats ( Balikci et al, 2020 ). In our next study, we have shown that tactile stimulations during the early postnatal period have a long-term impact on dendrite structure in WAG/Rij rat’s brain, and neonatal tactile stimulation can regulate dendritic spines in layer V in pyramidal neurons of SoCx which previously defined as the focus of epilepsy ( Ilbay et al, 2022 ). Although there are exciting results showing the positive effects of enriching tactile experiences in early life on absence epilepsy and accompanying depression-like behaviors in WAG/Rij rats, research on the effects of tactile experiences later in life does not exist.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…In a study done by our group we found that neonatal tactile stimulation slows down the development of absence epilepsy and comorbid depression-like symptoms in adult WAG/Rij rats ( Balikci et al, 2020 ). In our next study, we have shown that tactile stimulations during the early postnatal period have a long-term impact on dendrite structure in WAG/Rij rat’s brain, and neonatal tactile stimulation can regulate dendritic spines in layer V in pyramidal neurons of SoCx which previously defined as the focus of epilepsy ( Ilbay et al, 2022 ). Although there are exciting results showing the positive effects of enriching tactile experiences in early life on absence epilepsy and accompanying depression-like behaviors in WAG/Rij rats, research on the effects of tactile experiences later in life does not exist.…”
Section: Introductionmentioning
confidence: 81%
“…Then, an impartial evaluator assessed the duration of inactive swimming (immobility), the time it took for immobility to occur (immobility latency), and the overall amount of active swimming (swimming time) for each rat. Immobility is the state of being completely still, with no other movement save for the necessary action of keeping the head above water ( Balikci et al, 2020 ; Ilbay et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations